Comprehensive bibliography on agriculture and rural development - Shawkat Ali, A. M. M.; Khan, Mujibur Rahman (Dhaka, Bangladesh : University Press, 1994)
Chiefly with reference to Bangladesh.
Includes indexes.
Keywords: Agriculture -- Bangladesh -- Bibliography; Rural development -- Bangladesh -- Bibliography; Bangladesh -- Imprints